Контроль температурних режимів та охолодження тягових двигунів електротехнічних комплексів в процесі експлуатації - Некрасов, Андрій Вікторович; Чорна, Вікторія Олегівна; Кас'янов, Євгеній Михайлович (НТУ "ХПІ", 2016)
Проаналізовано відомі способи контролю температури обмоток тягових електричних двигунів. Розглянуто особливості функціонування існуючих пристроїв контролю температури тягових електричних двигунів рудничних електровозів та їх недоліки. Запропоновано спосіб безконтактного контролю та захисту тягових двигунів від перевищення температури. Розглянуто існуючі способи охолодження тягових двигунів. Встновлено недоліки існуючої системи охолодження тягових двигунів. Запропоновано спосіб примусового охолодження двигунів за рахунок нагнітання повітря всередину двигуна та оцінена його ефективність. Запропоновані способи дозволять підвищити надійність тягових двигунів та подовжити терміни їх експлуатації.

The analysis of types of main and industrial railway transport, which is operated by the railway and enterprises of Ukraine, iscarried out. The main reasons for the rapid failure of critical elements of traction electrical systems were identified. The reliability of electric transport depends on the conditions of its operation and the availability of effective control and monitoring systems for the technical condition of the main equipment. The main elements of electric locomotives are traction electric motors. It is established that it is possible to increase the reliability of electric motors due to the qualitative control of the temperature state of the engines. The analysis of known methods for monitoring the temperature of winding of traction motors is carried out. Features of functioning of existing thermoregulating devices for traction motors are considered. A method for monitoring and protecting traction motors from extreme temperatures is proposed. The developed control method will allow controlling the temperature of the motor windings without using bulky and inaccurate devices. The analysis of existing cooling systems of traction engines is carried out and their shortcomings are established. A method for cooling the engine is proposed. The method consists in supplying air inside the engine through the holes in the bearing shield. By using this cooling method, it is possible to extend the life of the engine and increase its reliability.
Controlling temperature and cooled traction motors electrical systems during operation
Keywords: електровоз; обмотка якоря; обмотка збудження; датчик; вимірювач; температура; electric locomotive; armature winding; excitation winding